Correction: Han et al. Study on the Joint Toxicity of BPZ, BPS, BPC and BPF to Zebrafish. Molecules 2021, 26, 4180 - Ying Han; Yumeng Fei; Mingxin Wang; Yingang Xue; Hui Chen; Yuxuan Liu (Molecules, 2023)
In the original publication [...]